El papel del significado en una noción pragmática de verdad - Colomina Almiñana, Juan José (Revista de Filosofía, 2007)
In this paper, we try to show why a formal definition of truth is not satisfactory (first point). Later, we expound (second point) the polemic between Austin and Strawson about truth with the intention to show that both refer to different problems concerning truth and to prove that Austin did not lose this confrontation and that we can recover some elements of his investigation for making an adequate approach to this notion. We will complete our definition of truth using the latest thesis of Charles Travis and that will permit us to conclude with a semantic definition of truth for natural languages.